Crystallographic-orientation-dependent dissolution behavior of sapphire in anorthite liquid containing chromia - Park, JK; Kim, DY; Lee, HY; Blendell, J; Handwerker, C (AMER CERAMIC SOC, 2003)
A sapphire single crystal was put into anorthite powders containing Cr2O3 and then heat-treated at 1600degreesC. The resultant morphologies of the sapphire-anorthite-liquid interfaces were corrugated and quite different depending on the crystallographic orientation of the sapphire; all the planes perpendicular to the C-plane showed fingerlike morphologies, while long parallel segments were detached from the basal C-plane. The results were interpreted in terms of coherency-strain-induced instability of the solid-liquid interface (ISLI) caused by the alloying of Cr2O3 into sapphire. The difference in microstructural evolution depending on crystallographic orientation was explained in terms of strong anisotropy of the solid-liquid interface characteristics.
Keywords: GRAIN-BOUNDARY MIGRATION; DIFFUSIONAL COHERENCY STRAIN; PLATELIKE ABNORMAL GRAINS; PHASE-SINTERED ALUMINA; MO-NI ALLOY; MICROSTRUCTURAL EVOLUTION; INSTABILITY; INTERFACE; MORPHOLOGY; DIRECTION